The Digital Scholar - Weller, Martin (Bloomsbury Academic, 2011)
While industries such as music, newspapers, film and publishing have seen radical changes in their business models and practices as a direct result of new technologies, higher education has so far resisted the wholesale changes we have seen elsewhere. However, a gradual and fundamental shift in the practice of academics is taking place. Every aspect of scholarly practice is seeing changes effected by the adoption and possibilities of new technologies. This book will explore these changes, their implications for higher education, the possibilities for new forms of scholarly practice and what lessons can be drawn from other sectors.